Leituras e imagens do 11 de setembro: reavaliações da história em Falling Man (2007), de Don DeLillo e em Fahrenheit 9/11 (2004), de Michael Moore - Mariano, Márcia Corrêa de Oliveira [UNESP] (2012)
September 11 has originated a wide range of artistic manifestations which have not only searched for plausible explanations for the tragedy, but also tried to review the events. In this sense, this thesis aims at showing how a novel and a documentary reevaluate this episode. The attacks made the United States experience a strong sense of vulnerability, triggering reactions from the American government, who quickly established a new national security strategy, associated with the war on terror. This thesis analyzes the narrative strategies employed by the American author Don DeLillo in his novel Falling Man (2007) and by the filmmaker Michael Moore in the documentary Fahrenheit 9/11 (2004), as well as the way they approach socioeconomic and political factors that caused the tragedy in order to reevaluate it. The debate of the topics is based on texts concerning the relationship between literature and history, postmodern fiction, documentary aspects and issues on terrorism. This study contributes to enrich the discussion related to the events that led to the catastrophe and its aftermath, examining characters and groups linked to the September 11 terrorist attacks, revealing multiple truths subjected to social, ideological and historical conditions